A reflection-type vapor cell using anisotropic etching of silicon for micro atomic clocks. (28th June 2019) - Nishino, Hitoshi; Hara, Motoaki; Yano, Yuichiro; Toda, Masaya; Kanamori, Yoshiaki; Kajita, Masatoshi; Ido, Tetsuya; Ono, Takahito
Abstract: This paper reports the design, fabrication and evaluation of a reflection-type optical Rb vapor cell for chip-scale micro atomic clocks. To reduce the physical package height, the reflection-type vapor cell is developed, in which optical components can be mounted on one side of the vapor cell. A (100)-oriented Si wafer with a cut-off 9.74° toward [011] direction is used to make 45° mirrors by anisotropic wet etching. 90° mirrors are fabricated by Si deep reactive ion etching and surface planarization using H2 annealing. Following the detection of D1 optical absorption for Rb atoms, coherent population trapping resonance was observed.